REAKSI PASAR MODAL INDONESIA (BEI) TERHADAP RESHUFFLE KABINET - Uke Prajogo (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2013)
The capital  market  is one of the important  financial  sector in the economy of a country. The capital market  is one of the effective  means to facilitate  long-term  funds held  by the public  to be channeled   in productive   sectors.  Capital  market  as one of the economic  instruments  is influenced  by events that  contain  information  for investors.  In- creasingly  important  role of capital  markets  in the economy  of a country, the more sensi- tive the capital  market  to various  events around  him. This study aims to assess the capital market  reaction  to the announcement   of United  Indonesia  Cabinet  reshuffle  vol 2 which took  place  on  October   19, 2011.  This  research  is quantitative   descriptive.   Assessment Cabinet  Reshuffle  reaction  to the announcement   of the stock price movement  LQ45 done through  observation   of price  movements,   abnormal  returns  (abnormal  returns),  Capital Asset  Pricing  Model  (CAPM),  and to Varibility  Reward  Ratio  (RV) during  the observa- tion period of 14 days before and 14 days after the announcement  date. The results showed that the announcement   of the cabinet  reshuffle,  do not give too strong  an influence  on the movement  of stock prices,  this  is evidenced   in the average  stock  price  and the average abnormal  return  is experiencing   fluctuating  movements  in the period of United Indonesia Cabinet  reshuffle  Volume  2. There  is no visible  trend  of the market  overreacted   to the emergence   of a significant  price  fall or rise  significantly.   Based  on this, there  is no sig- nificantrelationship    between abnormal  returns before and after the cabinet reshuffle which was conducted  on October  19, 2011.  Pessimistic   attitude  toward  improved  market  per- formance  of the post-reshuffle   cabinet  ministers  are also an indication  that the market  is not  overl    action  resulted  in the  announcement   of the    overnment's   cabinet  reshuffle. This study also showed  that agriculture,  mining, and chemical  industry  base, a variety of industries,   finance  and trade  in services  and investment   sector  was  the most  good  for investment  because  of the calculation  CAPM  expected  return  E (Ri) produced  smaller than  the average  expected  return  is realized  (Av.Ri) per sector  and the  low share  price means  the right time to invest. For Industrial  and Chemical  sector is a sector that is at the top rank has a value of -0.15987  and is the most affected  sectors.  While a good stock for investment  is INTP, SMGR, KRAS,  and CPIN. Top ranked  stocks are INTP that has the highest     value    that    is  equal    to   -0.09966     and   is   the   most    affected     stocks.